Evidence of exposure to C. burnetii among slaughterhouse workers in western Kenya - Cook, Elizabeth A.J.; Glanville, William A. de; Thomas, Lian F.; Kiyong'a, Alice; Kivali, Velma; Kariuki, S.; Bronsvoort, B.M. de C.; Fèvre, Eric M. (Elsevier, 2021)
Q fever, caused by C. burnetii, has been reported in slaughterhouse workers worldwide. The most reported risk factor for seropositivity is the workers' role in the slaughterhouse. This study examined the seroprevalence and risk factors for antibodies to C. burnetii in slaughterhouse workers in western Kenya to fill a data gap relating to this emerging disease in East Africa. Individuals were recruited from all consenting slaughterhouses in the study area between February and November 2012. Information was collected from participating workers regarding demographic data, animals slaughtered and role in the slaughterhouse. Sera samples were screened for antibodies to C. burnetii using a commercial ELISA and risk factors associated with seropositivity were identified using multi-level logistic regression analysis. Slaughterhouse workers (n = 566) were recruited from 84 ruminant slaughterhouses in western Kenya. The seroprevalence of antibodies to C. burnetii was 37.1% (95% Confidence Interval (CI) 33.2–41.2%). The risk factors identified for C. burnetii seropositivity included: male workers compared to female workers, odds ratio (OR) 5.40 (95% CI 1.38–21.22); slaughtering cattle and small ruminants compared to those who only slaughtered cattle, OR 1.52 (95% CI 1.06–2.19). In addition, specific roles in the slaughterhouse were associated with increased odds of being seropositive, including cleaning the slaughterhouse, OR 3.98 (95% CI 1.39–11.43); cleaning the intestines, OR 3.24 (95% CI 1.36–7.73); and flaying the carcass OR 2.63 (95% CI 1.46–4.75) compared to being the slaughterman or foreman. We identified that slaughterhouse workers have a higher seroprevalence of antibodies to C. burnetii compared to published values in the general population from the same area. Slaughterhouse workers therefore represent an occupational risk group in this East African setting. Workers with increased contact with the viscera and fluids are at higher risk for exposure to C. burnetii. Education of workers may reduce transmission, but an alternative approach may be to consider the benefits of vaccination in high-risk groups.